Common shock, different paths? Comparing social policy responses to COVID‐19 in the UK and Ireland. (15th December 2020) - Hick, Rod; Murphy, Mary P.
Abstract: The UK and Ireland responded to the rapid health and economic impacts of COVID‐19 by supporting incomes through job retention and job loss instruments, However distinct policy legacies, political and institutional differences between the two countries mean critical differences in both the nature and the relative weight placed on these instruments. The UK income support package was announced in one go and centred on a generous, newly created Job Retention Scheme as well as an enhanced Universal Credit for people who became unemployed. Ireland, by contrast, created a new, more generous social security payment, the Pandemic Unemployment Payment, while a less prominent job retention scheme followed a week later. These initial decisions generated distinct policy dilemmas during a second round of policy changes, in which Ireland sought to reintegrate the more generous Pandemic Unemployment Payment into the mainstream welfare system, while UK sought to ensure that the Job Retention Scheme was only supporting retained (or "viable") jobs. A second wave of infections in October 2020, requiring new restrictions, led both nations to make substantial retreats from resolving these core policy dilemmas.